Review of Optimization of Constructional Strength and Profitability Using Pre-Fabrication Technology: Exploring the Role of Pre-Fabrication Technology in Optimizing Construction Strength and Profitability (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The technology involving the fabrication and pre-assembly of constructional elements and components before they are installed into their final location. The precedent of prefab industry is the significant for the development of new technology in construction business of any nation. The present age demands a great need for affordable and fast housing facilities so the projects need to be completed at competitive fast rates. Conventional construction methods fail to deliver the desired speed of construction. So we opt for some other methods of construction. Total time of construction can be lowered through application of be precast construction. Despite of the advantageous features of fast and speedy erection, low cost precast construction. Components and structures made using prefabrication are increasingly directed to improving technology to achieve low cost and fast construction in the construction industry. Application trend of prefabricated components can aid a much faster output for the ever increasing construction demand in urban areas. Through mechanization promotion and application of prefabrication technology to create new employment opportunities and new ideas in construction. The study highlights the influence of prefabrication technology on the construction profitability and its effect in the work cycle time in construction detail review and study of literature and research work indicated that prefabrication is an emerging , innovative technology generally existing in developed nations, in which various materials are joined to fabricate a final component before installation. The main benefit of prefabrication is saves construction time, reduces construction throw away, together with improved quality. It is prominently observed that the building cost of structures using prefab technology is significantly less and duration of construction is also much diminishing as compared to traditional constructional method. Lowering the undesirable influence or impact of the construction methods on environment can be considerably lowered using the eco-friendly prefabrication technology. Sustainability and stringent quality control are attainable through prefabrication technology. Study is conclusive that the prefab technology is economical. Social and economic progress can be attained towards sustainability by application of the prefabrication technology.Although construction cost is a dominating constraint in affordable shelters, their durability and strength are equally important. Project aims at evaluating various pr-fabrication technology on their role with perspective of strength -durability and cost. Optimization of the various parameters using Minitab software the optimal technology will be proposed. Grey relation analysis will be carried out to predict the profitability of structures maintaining desired strength and durability.